Annual variation rate of KL-6 for predicting acute exacerbation in patients with rheumatoid arthritis-associated interstitial lung disease. Issue 6 (2nd November 2021) - Tanaka, Nozomi; Nishimura, Keisuke; Waki, Daisuke; Kadoba, Keiichiro; Murabe, Hiroyuki; Yokota, Toshihiko
Abstract: Objectives: This study evaluated the prognostic factors for acute exacerbation (AE), including sequential changes in Krebs von den Lungen-6 (KL-6) levels, in rheumatoid arthritis-associated interstitial lung disease (RA-ILD) patients. Methods: This was a retrospective observational study. We reviewed 125 patients diagnosed with RA-ILD between 2010 and 2019. We defined ΔKL-6 as the annual variation rate of KL-6 one visit before AE onset (or the last visit). The Cox regression analysis was used for evaluating significant variables associated with AE. We analysed the overall survival and respiratory-related death-free survival. Results: Thirty-three patients (26.4%) developed AE during the observation period. The univariate analysis revealed that KL-6 levels at RA-ILD diagnosis [hazard ratio (HR), 1.11; 95% confidence interval (CI), 1.05–1.15; p  < .01) and ΔKL-6 (HR: 3.69; 95% CI: −1.36 to 7.96; p =  .01] were significantly associated with AE. ΔKL-6 was an independent prognostic factor for AE in the multivariate analysis (HR: 3.37; 95% CI: −1.16 to 8.87; p =  .03). Patients with AE had a significantly higher overall mortality rate ( p =  .02) and respiratory-related mortality rate ( p <  .01) than those without AE. Conclusion: ΔKL-6 can be a prognostic marker for detecting AE in RA-ILD patients.